Clinical profile of patients with intussusception in a tertiary care institution in South India - San, Diljith; P., Ranjit; Ainippully, Arun M. (International Surgery Journal, 2020)
Background: Intussusception is a common abdominal emergency in children. It is the most common cause of intestinal obstruction in children less than 2 years. Awareness about the clinical presentation vomiting, abdominal pain, blood in stools, abdominal mass helps in early diagnosis. This study describes the demographics and clinical profile of patients with intussusception in a tertiary care institute in South India. Methods: This was a prospective case series study conducted in the pediatric surgery department in a tertiary care hospital in South India. Children upto 12 years with clinically and radiologically confirmed intussusception were enrolled over 12 months study period. Demographic and clinical data was collected and recorded. Results: Eighty two children with clinical and radiological picture suggestive of intussusception were studied. 57 patients (75%) were below 1 year of age. Male:female ratio was 1.7:1. The classical triad of abdominal colic, palpable abdominal mass and rectal bleeding was seen in 39 patients (50%). Most common signs were rectal bleed and abdominal mass. Conclusions: Awareness about the clinical presentation of intussusception helps in early diagnosis and prompt treatment of this common pediatric emergency and helps to prevent mortality.